Prospect of payments for environmental services in the Blue Nile Basin: examples from Koga and Gumera watersheds, Ethiopia - Alemayehu, B.; Hagos, Fitsum; Haileslassie, Amare; Mapedza, Everisto D.; Awulachew, Seleshi Bekele; Peden, Donald G.; Tafesse, T. (2009)
In transboundary river basins, like the Blue Nile, conflicts over the use of water resources are growing and recent advances in sustainable resource management recognizes the need for approaches that coordinate activities of people dependent on a common resource-base to realize sustainability and equity. Payments for Environmental Services (PES) are a component of a new and more direct conservation paradigm and an emerging concept to finance conservation programs by fostering dialogue between upstream and downstream land users. Those kinds of approach are particularly useful if applied in basins where irrigation schemes are emerging and the service life of reservoir and irrigation canals, in downstream areas are threatened by the sediments moved from upstream region. Here we report the results of our study on the determinants of Willingness to Pay (WTP) and Willingness to Compensate (WTC) for improved land and water management practices in the Blue Nile Basin (Gumera and Koga watersheds). A total of 325 sample households were selected using a multi-stage sampling technique, and a structured and pre-tested questionnaire was used to collect data from the sample households. We applied Contingent Valuation Method (CVM) to elicit WTP using monetary and material payment vehicles. Our results showed that more households are willing to pay in labor than in cash. The mean WTP for improved land and water management was estimated at US$1.06 and US$1.3 months-1 household-1 for upstream and downstream farmers, respectively. Besides, 83.56% of the sample farm households showed WTC the upstream farmers in cash. However, the aggregate WTP falls far short of the estimated investment cost needed for ecosystem restoration. Among others, the number of livestock, size of arable land, access to education and credit by the sample farm households were identified to positively influence sample farmers? WTP for restoration of ecosystem services and downstream farmers? WTC for improved ecosystem regulation services. Therefore, institutions and policy measures that enhance environmental education, reduce poverty and foster stakeholders? cooperation must be promoted. Prospect of Payments for Environmental Services in the Blue Nile Basin: Examples from Koga and Gumera Watersheds.